2019
DOI: 10.1103/physreva.99.062512
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion forces in inhomogeneous planarly layered media: A one-dimensional model for effective polarizabilities

Abstract: Dispersion forces such as van der Waals forces between two microscopic particles, the Casimir-Polder forces between a particle and a macroscopic object or the Casimir force between two dielectric objects are well studied in vacuum. However, in realistic situations the interacting objects are often embedded in an environmental medium. Such a solvent influences the induced dipole interaction. With the framework of macroscopic quantum electrodynamics, these interactions are mediated via A PREPRINT -JUNE 5, 2019Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Our calculations assumed a structureless continuum medium. It is possible, however, to incorporate a spatial structure into dispersion calculations …”
Section: Discussion: Impact Of the Model On Physical Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our calculations assumed a structureless continuum medium. It is possible, however, to incorporate a spatial structure into dispersion calculations …”
Section: Discussion: Impact Of the Model On Physical Effectsmentioning
confidence: 99%
“…It is possible, however, to incorporate a spatial structure into dispersion calculations. 74 Lastly, an unavoidable question is how much the water dielectric function will change when very close to the phase transition from the liquid to the solid state, leading to effects for the dielectric function for quasi-liquid water at the triple point not accounted for by considering cold liquid water only.…”
Section: Discussion: Impact Of the Model Onmentioning
confidence: 99%
“…The cavity type used for PCM calculations was a scaled VDW which places a sphere around each solute atom with the universal force field (UFF) radii 53 scaled by a factor of 1.1. The scaling factor depends on solvent, solute 36 , and the definition of atomic radii 54,55 . Examining the effects of the scaling factors, we found that the results with factor 1.1 fit well to the FIR spectrum at 4 K and can account for temperature-dependent spectral changes.…”
Section: Methodsmentioning
confidence: 99%
“…This assumption is questionable due to finite particle size leading to more complex models 283 and concerning the hard wall. 377,378 to point charges screening occurs also for dispersive interactions, where one expects screening by opt ) 2 with the frequency ω opt in the optical range for usual molecular systems. 374,379 Water has ε(ω opt ) ≈ 1.7, such that the screening is much less than for pure Coulomb fields.…”
Section: Polarisable Continuum Modelmentioning
confidence: 99%